Appraisal of African Union’s transformative objectives to the Africans: a qualitative study / Muritala Dauda, Mohammad Zaki Ahmad and Mohammad Faisol Keling - Dauda, Muritala; Ahmad, Mohammad Zaki; Keling, Mohammad Faisol (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
The need to revitalize the continental organisation in Africa is the reason behind the transformation of AU from OAU. The officially inauguration of the AU on 9th July, 2002 marked the turning point in the Africa history from all sorts of political instability, insecurity, prevalent poverty rate, epidemic of deadly diseases, among others, which the continent had experienced under OAU. The AU’s objectives emanated from the weakness of the OAU to strengthen the former. The study appraises AU for the mechanisms put in place to ensure peace, stability and development in the African continent. The research findings observe that measures introduced by AU to address the challenges confronting Africa which include – the replacement of Non-Interference Policy to Policy of Non-Indifference, Respect for Rule of Law, establishment of Peace and Security Council, formation of African Peer Review Mechanism, Abolition of Trade barriers among others has assisted in uniting the African continent. The study adopts functionalism theory to express the uniqueness of cooperation and unity towards ensuring stability and development in Africa. The importance of harnessing economic resources to ensure buoyant regional integration preaches by the theory has made it relevant to the study. The research is a qualitative that uses both primary and secondary data sources. Interview method as primary source of data for this study was generated from professional views of respondents from Nigerian government parastatals and higher institutions of learning, and the interview data was thematically analysed with the aid of NVivo 10. The secondary data for this research was sourced through relevant materials such as books, journal articles, policy documents, and newspapers.